Analisis Kompetensi Pedagogik Guru PAUD dalam Implementasi Technological Pedagogical Content Knowledge (TPACK) Pada Pembelajaran di Kelas - Afifah Nuranti; Farikhatun Nabila; Natalia Kristiany Nababan; Rahmatullah Rahmatullah; Rita Kurnia (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Pedagogical competence needs to be adjusted to the application of technology so that the educational process does not solely depend on devices, but also focuses on achieving children's developmental goals. Therefore, a deep understanding of the Technological Pedagogical Content Knowledge (TPACK) framework, reinforced by solid self-efficacy, is an essential requirement for early childhood educators to transform the potential of technology into superior pedagogical standards. The purpose of this study is to explore the pedagogical competency challenges faced by educators in Class A of the PG LAB FKIP UNRI kindergarten in applying learning technology. The research method used is descriptive qualitative. The results of this study indicate that the introduction and use of technology should be a necessity in creating learning that is relevant and adaptive to the demands of the times. Teachers are required to constantly update their skills in using digital technology to be more creative and innovative in teaching so that an optimal learning process can be achieved.